Time for tea: factors of service quality, memorable tourism experience and loyalty in sustainable tea tourism destination - Ng, Siew Imm; Lim, Xin Jean; C., Michael Hall; Tee, Keng Kok; Kamal Basha, Norazlyn; Ibrahim, Wan Siti Nabilah; Koupaei, Sara Naderi (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Underpinned by Script Theory and the S-O-R model, this research enhances the green tourism consumption literature to identify how destination service quality contributes to visitors’ memorable experiences and loyalty towards a place-based food tourism attraction. A total of 202 tourists who visited the Best of Highlands tea plantation in Malaysia were surveyed using an online questionnaire. Using PLS-SEM, this study has several notable findings: (i) destination service quality factors: activities, cleanliness, language, and security emerged as predictors of memorable tourism experiences; (ii) memorable tourism experiences strongly predicted destination loyalty; and (iii) memorable tourism experiences mediate the path between destination service quality and destination loyalty. This study therefore provides new insights into both sustainable tea tourism and script theory with respect to how memories guide future decision making. These results also provide insights for tea tourism providers in designing an unforgettable destination that stimulates the tourist’s intention to revisit the destination and to communicate it to others.